Evaluación y rehabilitación neuropsicológica en oncología pediátrica - Bernabeu, Jordi; Cañete, Adela; Fournier, Concepción; López, Beatriz; Barahona, Tina; Grau, Claudia; Tórtola, Angela; Badal, Mª Dolores; Álvarez, Jose A.; Suárez, Jesús M.; Castel, Victoria (Psicooncología, 2003)
Objective. The aim of this paper is to understand the neuropsychological long-term effects of childhood cancer and its treatments. We include a proposal for cognitive rehabilitation. Method. Method consists of a systematic review of scientific literature results on chemo- and radiotherapy effects on CNS plus cognitive and behavioural functions detected through neuroimage studies as calcifications and white matter changes. We also present a neuropsychological assessment protocol exemplified with a common diagnosis showing generalized impairment. Moreover, we propose a rehabilitation program based on Attention Process Training (APT) by Mateer & Sohlberg. Results. Cranial radiotherapy and methotrexate produce generalized impairment reflected in neuropsychological deficits: IQ, attention, memory, motor and academic skills. Conclussions. Treatment development implies a reduction in sequelae. Nevertheless, cognitive and behavioral problems are frequent in CNS tumors and leukemias. Periodic neuropsychologic assessment and recent white matter models help us to understand these long-term effects. Hence, this evaluation is basic to diagnose more accurately those deficits avoiding false attributions and inadequate expectations. We emphasize the need of a follow up unit working in on interdisciplinary manner to promote a better quality of life in children with cancer.